Identifikasi Spesies Ikan Hiu dan Pari pada Produk Olahan Ikan Asap dengan Metode DNA Barcoding : Identification of Shark and Sting Fish Species in Smoked Fish Processed Products Using The DNA Barcoding Method - Misla Alfitri; Asadatun Abdullah; Roni Nugraha (Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2022)
Sharks and rays are a group of fish whose trade is regulated both locally and internationally. The high demand for shark products in the market can result in the scarcity of certain shark species in the wild. Authentication on processed shark products is needed to detect the type of shark species used in a product. The purpose of this study was to identify species of sharks and rays in processed smoked products originating from the PANTURA, Tegal Jawa Tengah using the DNA barcoding method. The research method consisted of sample collection, DNA isolation, DNA extraction, DNA concentration and purity, PCR amplification and sequencing, Electrophoresis, Sanger Sequencing, PCR testing with COI molecular marker, and analysis of bioinformatics data. Species identification results from processed products of stingrays and smoked sharks were detected using sharks, including Carcharhinus brevipinna, Telatrygon zugei, Rhizoprionodon oligolinx, Himantura uarnacoides, Maculabatis macrura, Hydrolagus novaezealandiae, and Rhynchobatus australiae. Rhynchobatus australiae and Carcharhinus brevipinna are species listed as a protected shark in CITES II. The sequences obtained have a similarity percentage between 99.84-100% with the sequences found in GenBank.